Characterization of the anisotropic deformation of the right ventricle during open heart surgery. Issue 3 (17th February 2020) - Soltani, A.; Lahti, J.; Järvelä, K.; Laurikka, J.; Kuokkala, V.-T.; Hokka, M.
Abstract: Digital Image Correlation (DIC) was used for studying the anisotropic behavior of the thin walled right ventricle of the human heart. Strains measured with Speckle Tracking Echocardiography (STE) were compared with the DIC data. Both DIC and STE were used to measure longitudinal strains of the right ventricle in the beginning of an open-heart surgery as well as after the cardiopulmonary bypass. Based on the results, the maximum end-systolic strains obtained with the DIC and STE change similarly during the surgery with less than 10% difference. The difference is largely due to the errors in matching the longitudinal direction in the two methods, sensitivity of the measurement to the positioning of the virtual extensometer of in both STE and DIC, and physiological difference of the measurements as the DIC measures the top surface of the heart whereas the STE obtains the data from below. The anisotropy of the RV was measured using full field principal strains acquired from the DIC displacement fields. The full field principal strains cover the entire region of interest instead of just two points as the virtual extensometer approach used by the STE. The principal strains are not direction dependent measures, and therefore are more independent of the anatomy of the patient and the exact positioning of the virtual strain gage or the STE probe. The results show that the longitudinal strains alone are not enough to fully characterize the behavior of the heart, as the deformation of the heart can be very anisotropic, and the anisotropy changes during the surgery, and from patient to patient.